Bioaccumulation Of Copper And Its Effect On Humoral Immune Response In Goldfish Carassius Auratus Linnaeus - Hossain, Md.Abul (1990)

(untitled)
This study reports on the a cute toxicity levels , bioaccumulation of copper and their effect son the humora limmune response of gold fish ( Carassius auratus ) . This study also provides in formation on the level sof bio accumulation of copper in organs such as kidney , live rand spleen , which plays a role on the humoral antibody production of gold fish under tropical conditions . The a cute toxicity levels of copper to gold fish (10.5 ± 1.43 g ) for 12 , 24 , 48 , 72 , 96 and 120 hours were estimated as 0.44 ± 0.06 , 0.36 ± 0.04 ,0. 20 ± 0.03, 0.19 ± 0 . 02,0. 15± 0.02 and 0.14 ± 0 . 02 ppm respectively under fresh water static conditions.